First record of the fossil snakefly genus Mesoraphidia (Insecta: Raphidioptera: Mesoraphidiidae) from the Middle Jurassic of China, with description of a new species - Lü, Ya-Nan; Liu, Xingyue; Dong, Ren (Zootaxa, 2015)
Mesoraphidia daohugouensis sp. nov. is described from the Middle Jurassic Jiulongshan Formation of Inner Mongolia, China. It is diagnosed by the following character states: subquadrate pronotum, narrowly elliptical forewing, distally darkened pterostigma closed respectively by a proximal costal crossvein and a distal radial veinlet, absence of pterostigmal crossvein. The new species represents the first record of Mesoraphidiinae from the Middle Jurassic of China.